In-depth evaluation and enhancement of a PV-wind combined system: A case study at the Engineering Faculty of Wahid Hasyim University - Mauludin, Moch Subchan; Khairudin, Moh.; Asnawi, Rustam; Trisnoaji, Yuki; Prasetyo, Singgih Dwi; Azizah, Safira Rusyda; Wiraguna, Rayie Tariaranie (Institute of Advanced Engineering and Science, 2025)
Energy sustainability is crucial for mitigating climate change and reducing dependence on fossil fuels. This research evaluates a hybrid renewable energy system combining photovoltaic (PV) technology and wind turbines to meet the electricity demand of Wahid Hasyim University's Faculty of Engineering, totalling 555,000 VA. Using HOMER Pro software, the study identifies the optimal configuration based on technical, economic, and environmental aspects. The hybrid system integrating PV, wind turbines, batteries, and converters achieves the lowest Net Present Cost (NPC) of 214,877 and a Levelized Cost of Energy (LCOE) of 0.0185/kWh, outperforming grid-only systems. Environmentally, the system significantly reduces carbon dioxide (CO2) emissions, from 559,226 kg/yr in conventional systems to 62,452 kg/yr. Solar energy contributes 56% of electricity generation, leveraging stable solar radiation of 4.28–5.54 kWh/m²/day. Additionally, an annual surplus of 156,350 kWh can be sold back to the grid, enhancing operational efficiency. This study demonstrates that hybrid renewable energy systems deliver long-term cost efficiency and significantly mitigate climate impacts. It provides a sustainable energy model for campuses in Indonesia and worldwide, particularly in regions with abundant solar resources.